COVID-19 International Horizon Scanning – informing a response and recovery in Wales and beyond. (20th October 2021) - Stielke, A; Bowles, C; Couzens, L; Cotter-Roberts, A; Allen, J; Van Eimeren, M; Bainham, B; Dyakova, M
Abstract: Issue: The rapidly evolving nature and uncertainties of the COVID-19 pandemic have led to unprecedented challenges for health systems, as well as to wellbeing, social and economic impacts for individuals and communities across the globe. Effective, dynamic, innovative and evidence-based solutions are needed to address these challenges. Description of Problem: The World Health Organization (WHO) Collaborating Centre on Investment for Health and Well-being, Public Health Wales, has initiated and continues to perform International Horizon Scanning work to inform the evolving COVID-19 public health response and recovery plans in Wales by learning from best practices from other countries. The learning and intelligence is systematically synthesized in rapid regular reports published every week/two weeks. The focus and scope vary, depending on the COVID-19 situation and public health and policy needs. Results: The work stream has provided Welsh Government, the National Health Service (NHS), Public Health Wales and other key stakeholders with continuous and timely learning from the experience of other countries along with emerging evidence and guidance, provided by key international organisations. This includes international evidence, epidemiological data, experience, measures and recovery approaches, to understand and explore solutions. Reports have given a consistent overview of approaches across countries such as a comparative analysis of the vaccine roll-out or a systematic overview of the R-value and measures implemented accordingly. Lessons: To understand, mitigate and address the impacts of the pandemic in Wales and beyond, a timely, dynamic and evidence-informed actionable intelligence has proven to be essential to inform and support decision-making on government and health system level to address the pandemic and mitigate harms from COVID-19. Key messages: International learning has and continues to inform the evolving COVID-19 public health response in Wales. Public Health Wales is contributing to an evidence-informed inclusive recovery from the pandemic in Wales and beyond.